2012
DOI: 10.4103/0019-5154.97681
|View full text |Cite
|
Sign up to set email alerts
|

Giant seborrheic keratosis of the genitalia

Abstract: Genital seborrheic keratosis (SK) is a rare entity, which can be easily misdiagnosed as genital warts. Dermoscopy is a useful tool to make diagnosis of SK in such cases. We report a 50-year-old woman with a large polypoidal growth on the external genitalia. Dermoscopic examination showed fissures and ridges, cerebriform appearance, and comedo-like openings consistent with SK. The histopathology confirmed the diagnosis of SK.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…More than one type is often found in the same lesion [ 7 ]. Basal cell carcinoma, condyloma acuminata, melanoma are the most common misdiagnoses of seborrheic keratosis [ [2] , [3] , [4] , [5] ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…More than one type is often found in the same lesion [ 7 ]. Basal cell carcinoma, condyloma acuminata, melanoma are the most common misdiagnoses of seborrheic keratosis [ [2] , [3] , [4] , [5] ].…”
Section: Discussionmentioning
confidence: 99%
“…SK involving the genital region is a rare scenario, and can be easily misdiagnosed as genital warts. Histopathology helps in making the diagnosis in such cases [ 3 ]. Lesions are rarely more than 3 cm in diameter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Giant SK, an atypical SK, is rarely reported on the genitalia, perianal, or face in previous studies (14)(15)(16)(17). However, at the time of this study, no case of giant SK was reported on the flank part.…”
Section: Discussionmentioning
confidence: 55%
“…Extensive female genital involvement was also reported. [ 7 ] There was also a report of giant pedunculated lesion occurring over the groin. [ 8 ] However, such extensive involvement as in our case with lesions over the pubic area, genitals, scrotum, perineum, thigh, and perianal areas has not been documented previously.…”
Section: Discussionmentioning
confidence: 99%